Transmission of Triaenophorus crassus from copepod first to coregonid second intermediate hosts and effects on intermediate hosts - Pulkkinen, Katja (1999)
Factors affecting transmission of Triaenophorus crassus (Cestoda) from copepod first to coregonid second intermediate hosts were studied using field data from three areas at Lake Saimaa, SE Finland, as well as data from experimental infections of hosts in the laboratory. In Lake Saimaa whitefish (Coregonus lavaretus s.l.) were frequently infected with T. crassus plerocercoids, but vendace (C. albula) only accidentally. Stomach samples indicated that both fish species consumed copepod species that were suitable as hosts. In experimental infections whitefish became infected with T. crassus but vendace did not. Abundances of a benthically transmitted nematode Cystidicola farionis in whitefish indicated that as a superior competitor for planktonic food, vendace, when abundant, may displace whitefish from feeding on plankton and force it to rely more on benthic food. Vendace stock strength did not, however, affect the abundance of T. crassus in whitefish. This is possibly due to synchronization of the transmission of the parasite to the seasonal feeding behaviour of coregonids in spring in the littoral zone, when copepods are the only abundant food available for both whitefish and vendace. Vendace, however, do not become infected even though they eat infected copepods, since T. crassus is less infective for vendace than whitefish. In the first intermediate host (Cyclops strenuus), T. crassus infection affected the copepod's feeding, fecundity and survival and caused changes in swimming behaviour and microhabitat selection and an increased susceptibility to predation by whitefish juveniles in the laboratory. However, evidence that the behavioural alterations in copepods were caused by active manipulation adaptive to the parasite was not clear. In whitefish, the accumulation of the plerocercoids seemed to increase in the oldest hosts, in which also the effects of T. crassus infection on growth were concentrated. However, no evidence of parasite-induced mortality was found.